The expansion of the Cisplatine War to the African shore of the Atlantic - Oliveira, Marcelo Rodrigues de (2020)
In this article we will try to prove that the Cisplatin war (1825-1828) originated needs of protection in the Transatlantic Trade of african slaves to Brazil, because privateers of the united provinces of the River Plate crossed the Atlantic aiming to capture the slave ships destinated to Brazil. In 1827, in the climax of the Corso War, the Imperial government ordered the establishment of a Naval Force in the Angola coast with the purpose to warrant the safeguard of ships engaged in “The Souls Trade”.